Handbook of research methods in public administration - Yang, Kaifeng; Miller, Gerald (Public administration and public policy series, 2008)
Explores how systematic research methods could aid in understanding traditional questions in public administration as well as theoretical and practical questions. This book offers encyclopedic treatment of research designs with case studies; surveys research designs used in public administration and relates these designs to analytical methods.